Implications of China’s Approved Tourism Destination Status (ADS) on Zimbabwe’s Tourism Environment: Insights from Local and Government Tourism Groups in Zimbabwe - Zhou Zibanai (AFRICAJOURNALS, 2023)
This study examined system-wide implications of an Approved Destination Status (ADS) granted to Zimbabwe by China in 2004 on Zimbabwe`s tourism industry. A total of 150 self-administered questionnaires were used to collect data. The study revealed a disproportionate increase of tourism traffic from the Chinese market and revenue inflows which have largely remained depressed. Findings further highlighted that Chinese`s low spending patterns, inaccessibility of the country, and a highly volatile political environment have undermined the ADS. The ADS dispensation has presented local operators with a dilemma on the way forward, hence a shift in marketing strategy, re-configuration of the pricing regime, and improved air connectivity are necessary.